(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2022)
Equality of citizens on the grounds of gender is guaranteed under Article 8(2) of the Federal Constitution and international human rights treaties. Despite this guarantee of right, transgender people claim that they are still discriminated and receive unequal treatment, especially when accessing health care. Therefore, the objective of this study is to determine the extent to which the existence of domestic laws and international laws have placed the highest standard of treatment for individuals with gender identity disorder or transgender people in Malaysia. The methods used in completing this study were through referrals and interviews. In this study, the researcher successfully found that the right to equality guaranteed under the Federal Constitution is not absolute and is subjected to other relevant laws. The researcher also managed to identify several alternatives that can be employed to solve the problems related to discrimination against transgender people, namely with more stringent law enforcement and actions by the Malaysian government on health practitioners in the event of discriminatory treatment against transgender people. Keywords: Transgender, equality, domestic law, international law, Ministry of Health Malaysia, Federal Constitution Full text: PDF